Effects of intercropping maize (zea mays) with butternuts (cucurbita moschata) at varying butternut population levels on maize growth, yield and weed supression - Muperi, Serita (Midlands State University, 2017)
Intercropping is a cultural technique which gives crops a competitive advantage on weeds therefore contributes to weed management. There is need to choose the plant population which results in weed suppression whilst not negatively affecting the component crops yield. The experiment was set in a Randomised Complete Block Design with 5 treatments which are sole maize crop, maize-butternut intercrops at butternut densities of (30%, 40% and 50% of maize population which is 11110, 13889 and 18518plants/ha respectively) and sole butternut crop. Data on maize plant height, maize grain yield, weed density and biomass were measured and Land Equivalent Ratio (LER) calculated using yields of maize and butternut. It was found that there was no significant difference on maize plant height and weed density. However, there was significant (P<0.05) differences on maize grain yield, (P<0.05) on weed biomass and (P<0.05) on LER. Intercropping maize-butternut at different population levels results in different effect on maize grain yield, weed biomass and LER. Maize grain yield first increases with increase in butternut population density from 11110 plants/ha to 13889 plants/ha and then decreases as population continues to increase from 13889 plants/ha to 18518 plants/ha. Weed biomass decreases as butternut population density increases from 11110 plants/ha to 18518 plants/ha. LER values decreases as butternut population density increases from 11110 plants/ha to 18518 plants/ha. Intercropping maize and butternuts at 13889 plants/ha produce higher maize grain yield than the other intercrops and was similar to sole maize yield, have low weed biomass and also have higher LER. I recommend farmers to intercrop maize-butternut at 13889 plants/ha which produces high yield, have higher impact on weed suppression and have higher land productivity. Further research should be carried out on different crop geometry which can reduce effect of competition between crops.